2011
DOI: 10.1016/j.str.2011.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Domain Orientation in the N-Terminal PDZ Tandem from PSD-95 Is Maintained in the Full-Length Protein

Abstract: Tandem PDZ domains have been suggested to form structurally-independent supramodules. However, dissimilarity between crystallography and NMR models emphasize their malleable conformation. Studies in full length scaffold proteins are needed to examine the effect of tertiary interactions within their native context. Using single molecule fluorescence to characterize the N-terminal PDZ tandem in PSD-95, we provide the first direct evidence that PDZ tandems can be structurally-independent within a full-length scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 51 publications
2
56
0
Order By: Relevance
“…If local structure existed, we would have expected a dispersion of FRET values (37). Instead, the results showed minimal positional dependence and instead the FRET scaled linearly with the fluorophore separation.…”
Section: Discussionmentioning
confidence: 89%
“…If local structure existed, we would have expected a dispersion of FRET values (37). Instead, the results showed minimal positional dependence and instead the FRET scaled linearly with the fluorophore separation.…”
Section: Discussionmentioning
confidence: 89%
“…The narrow smFRET peak widths and lack of signal variance suggest rapid dynamics across the PDZ2-3 linker (13). Measurements between PDZ1 and PDZ2 was measured previously (44). VMF characterizes replicate measurements using different labeling sites to oversample the domain position.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant protein samples were purified and fluorescently labeled with a mixture of Alexa Fluor 555 C 2 maleimide and Alexa Fluor 647 C 2 maleimide as described previously (44). PSD-95 was encapsulated in 100 nm liposomes, which were immobilized to a quartz slide for Total Internal Reflection illumination with alternating laser excitation at 532 nm (approximately 7.5 mW before prism) and 633 nm (approximately 3 mW before prism).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands approaching from the same direction seem to be preferably bound by the PDZ domains oriented in parallel. However, measurements based on single-molecule fluorescence suggest an antiparallel orientation of binding sites favouring the interaction with ligands from opposite directions (McCann et al, 2011). A more recent transmission electron microscopy (TEM) based study showed that PSD-95 and cytoplasmic domains of Kir2.1 build up 1:1 complexes, which are able to tetramerize into self-enclosed structures (Fomina et al, 2011).…”
Section: Discussionmentioning
confidence: 99%